Kemampuan Berpikir Kreatif Matematis Sekolah Dasar Ditinjau Dari Gaya Belajar Auditorial - -, Astuti; Dewi Puji Rahayu; Syahfitriani Br Ginting; Serlina Boru Sinaga; Paustina Ngali Mahuze; Rival Hanip; Roberto W. Marpaung; Prima Lestari Situmorang (Jurnal Pendidikan Modern, 2024)
The research intends to analyze the creative thinking abilities of students with an auditory learning style. The research method used is qualitative because it contains descriptions of creative thinking abilities in 3 categories, namely low, high and medium. The research included 35 students in class IV. Data was obtained from the results of tests on creative thinking abilities that had been prepared and non-tests in the form of learning style classification questionnaires. The results of the research show that students with an auditory learning style who have low thinking abilities almost meet flexibility; fluency and detail possessed by students with creative abilities while auditory learning style; then students with high creative abilities have an auditory learning style that meets flexibility and almost meets fluency.